Stability of nanofluid: A review. (25th June 2020) - Chakraborty, Samarshi; Panigrahi, Pradipta Kumar
Highlights: Stability of nanofluid is a critical factor which influences its applicability. Significant research gap exists in implementation of different stabilization techniques. Wall effect on stability should be considered in microfluidics and porous media application. Salinity effect must be considered for EOR application of nanofluid. More studies on hybrid nanofluid stability and quantum dots are warranted. Abstract: Nanofluid is a suspension of nanoparticles (at least one dimension less than 100 nm) in a basefluid having superior thermal, rheological and wettability properties, which improves the performance of several applications i.e. heat transfer, lubrication, drug delivery and enhanced oil recovery etc. However, the critical bottleneck for widespread use of nanofluid is its stability. The instability of nanofluid leads to reduction in system performance with passage of time. Addressing the long term stability of nanofluid and its reusability are essential requirements for successful industrial use. This article focuses on different aspects of nanofluid stability starting from the preparation stage till implementation in practical applications. Specific attention has been given on nanofluid stability as a function of operating conditions i.e. high temperature, pressure, confinement, composition, salinity, external magnetic field and shear rate etc. in several applications i.e. heat transfer, microfluidics, lubrication, enhanced oil recovery and drag reduction etc. It is expected that the present review will provide guidance and contribute towards wider adoption of nanofluid in practical applications. Future research on stability issues related to techno-economic performance, hybrid nanofluid, quantum dot, hybrid stabilization technique, wall effect in microfluidics and porous media will further enhance the usability of nanofluid in widespread practical systems.